The Diguanylate Cyclase SadC Is a Central Player in Gac/Rsm-Mediated Biofilm Formation in Pseudomonas aeruginosa - Moscoso,JA; Jaeger,T; Valentini,M; Hui,K; Jenal,U; Filloux,A (Journal of Bacteriology, 2014)
Pseudomonas aeruginosa is a Gram-negative opportunistic human pathogen and a threat for immunocompromised and cysticfibrosis patients. It is responsible for acute and chronic infections and can switch between these lifestyles upon taking an informeddecision involving complex regulatory networks. The RetS/LadS/Gac/Rsm network and the cyclic-di-GMP (c-di-GMP)signaling pathways are both central to this phenomenon redirecting the P. aeruginosa population toward a biofilm mode ofgrowth, which is associated with chronic infections. While these two pathways were traditionally studied independently fromeach other, we recently showed that cellular levels of c-di-GMP are increased in the hyperbiofilm retS mutant. Here, we have formallyestablished the link between the two networks by showing that the SadC diguanylate cyclase is central to the Gac/Rsmassociatedphenotypes, notably, biofilm formation. Importantly, SadC is involved in the signaling that converges onto the RsmAtranslational repressor either via RetS/LadS or via HptB/HsbR. Although the level of expression of the sadC gene does not seemto be impacted by the regulatory cascade, the production of the SadC protein is tightly repressed by RsmA. This adds to thegrowing complexity of the signaling network associated with c-di-GMP in P. aeruginosa. While this organism possesses morethan 40 c-di-GMP-related enzymes, it remains unclear how signaling specificity is maintained within the c-di-GMP network. Thefinding that SadC but no other diguanylate cyclase is related to the formation of biofilm governed by the Gac/Rsm pathway furthercontributes to understanding of this insulation mechanism.